Tribological behavior of composites fabricated by reactive SPS sintering in Ti‐Si‐C system. Issue 2 (17th December 2019) - Hadji, Youcef; Benamor, Abdessabour; Chiker, Nabil; Haddad, Adel; Tala‐Ighil, Nacer; Erauw, Jean‐Pierre; Dupont, Vedi; Tricoteaux, Arnaud; Nivot, Christelle; Thuault, Anthony; Hadji, Mohamed
Abstract: In this study, wear and friction behavior of two based‐composites from the Ti‐Si‐C system, (40 wt% TiC; 28 wt% Ti5 Si3 ; 17 wt% Ti3 SiC2 ) and (18 wt% TiC; 26 wt% Ti5 Si3 ; 41 wt% Ti3 SiC2 ) reinforced by 15 wt% of large size SiC (100‐150 µm) particles were investigated. The four‐phase composites exhibited approximatively the same friction coefficient (µ 0.9) under high loads (10 N and 7 N). The composite with high Ti3 SiC2 showed higher wear rate values by one order of magnitude. However, under 1 N, the composite with high TiC content showed a higher running‐in period and a lower steady state µ value (0.37 after 1000 m sliding distance). Scanning electron microscopy, Energy Dispersive X‐Ray and Raman spectroscopy analysis of the worn surfaces of the two composites revealed that oxidation was the dominant wear mechanism. The oxidation process and the removal kinetics of the oxides during sliding controlled the tribological behavior of the composites. The influence of processing variables on microstructures development and wear mechanisms of the composites is discussed.